Step-up to medicine - Ring, Adam C. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2016)
"The questions serve as a self-assessment tool, allowing students to think through clinical scenarios without answer choices influencing their thought process. Most questions end in "what are the appropriate next steps in managing this patient?" Imagine yourself as the clinician taking care of these patients: What test(s), if any, would you order next?"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Clinical Medicine -- Problems and Exercises